Alteraciones en el largo de la cola y su asociación con caracteres de fertilidad en ratones CF1 seleccionados por peso - Bernardi, S.F. (2011)
In a control population (t) and in two pairs of lines of two-way selection for body weight (s and h: downward selection; s' and h': upward selection), mice with tail alterations and absence of caudal vertebrae were presented with low frecuency from line foundation. To estimate the relations among tail length (LC), number of caudal vertebrae (V), weight (P) and fertility characters, LC was measured in mm, V was counted by X-rays, structural characters in ovaries and testicles were observed by optical microscopy. It was tested, by ANOVA and multiple comparisons tests, that lines differed in LC (p<0,05) in the same way of the weigth selection performed (males: LCh =8,4; LCs =8,8; LCt =9,0; LCh'=9,2; LCs'=9,8). The mice with caudal vertebrae absences (cc) had, in average, half of the V than the animals with phenotypically normal tails (cn). Males and females presented smaller gonads,minor seminiferous tubule diameter in males and minor number of corpora lutea in females, when cc animals were compared with cn ones (p<0,05). LC was modiffied as correlated response to the weight selection, but the presence of animales with tail malformations would be due to mutations that may be associated with fertility.